Recreational screen time and adolescents’ school adjustment based on latent profile analysis: The mediating role of perceived physical health - Jian Yang; Yuan Zhang; Ming Wu; Huiyu Shi; Bianjiang Zhang; Zhihui Li (PLoS ONE, 2025)
This study surveyed 12529 adolescents and employed latent profile analysis to explore the types of adolescents’ school adjustment. Multiple linear regression and the Bootstrap method were used to investigate the predictive role of recreational screen time in adolescents’ school adjustment and the mediating mechanism of perceived physical health. The results revealed three types of school adjustment in adolescents: “Ideal Type”, “Growth Type”, and “Ambivalent Type”. Recreational screen time was found to significantly and negatively predict both adolescents’ school adjustment and their classification into adjustment types. Furthermore, recreational screen time indirectly predicted adolescents’ school adjustment through the mediating role of perceived physical health. These findings suggest the importance of appropriately controlling recreational screen time, especially for adolescents in the ideal type category, and further exploring the physical and mental development patterns of adolescents in the ambivalent type, to provide a theoretical basis for improving school adjustment in adolescents.